Different antidumping legislations within the WTO: What can we learn from China's varying market economy status? - Alexander Sandkamp; Erdal Yalcin (Review of International Economics, 2021)
This paper examines how varying antidumping methodologies applied within the World Trade Organization differ in the extent to which they reduce targeted exports. We show that antidumping duties, on average, hit Chinese exporters harder than those of other targeted countries. This difference can be traced back in part to China's non-market economy status, which affects the way antidumping duties are calculated. Furthermore, we show that the type of imposed duty matters, as ad-valorem duties affect exports differently compared to specific duties or duties conditional on the export price. Overall, however, antidumping duties remain effective in reducing imports independent of market economy status.
Keywords: 330